Maritime networks as a vector for early farming/language dispersals: A comparative review - Mark Hudson; Junzo Uchiyama; Claudia Zancan; Katarina Šukelj; Renata Cabral Bernabé; Rasmus G. Bjørn; Ilona R. Bausch; Irene M. Muñoz Fernández (Quaternary Environments and Humans)
Maritime networks have been proposed as a mechanism for early agricultural and, by extension, language dispersals in several coastal and island regions. In Island Southeast Asia, such networks have sometimes been discussed as an alternative to the farming/language dispersal hypothesis. However, the relationships between Neolithic maritime networks and maritime economies are poorly known. Here, we summarise published information for three regions where Neolithic maritime networks are thought to have been associated with language dispersals (whether hypothetical or directly attested): the Mediterranean, Island Southeast Asia and Japan. We conclude that while maritime networks played an important role in the Neolithic dispersals considered here, maritime trade and resources did not necessarily represent alternative or opposing economic strategies to agriculture. It was only from the Bronze Age that long-distance trade integrated maritime exchange and resources into a broader economic system. Our review illustrates the complex relations between subsistence, technology and mobility in prehistoric maritime networks and the paper concludes with suggestions for future research.